2021
DOI: 10.3390/s21248386
|View full text |Cite
|
Sign up to set email alerts
|

Sputter Deposited Magnetostrictive Layers for SAW Magnetic Field Sensors

Abstract: For the best possible limit of detection of any thin film-based magnetic field sensor, the functional magnetic film properties are an essential parameter. For sensors based on magnetostrictive layers, the chemical composition, morphology and intrinsic stresses of the layer have to be controlled during film deposition to further control magnetic influences such as crystallographic effects, pinning effects and stress anisotropies. For the application in magnetic surface acoustic wave sensors, the magnetostrictiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The designed MPD is based on the cantilever-structured AlGaN/GaN high-electronmobility transistor (HEMT), in which a magnetic thin film ((Fe 90 Co 10 ) 78 Si 12 B 10 ) is deposited on the front end of the cantilever. [37][38][39][40] The enlarged part is the schematic cross-section of the AlGaN/GaN HEMT, where from top to bottom are AlGaN, AlN, GaN, and Si substrates. The thicknesses of AlGaN, AlN, and GaN layers are 30 nm, 1 nm, and 4.3 µm, respectively, and the active region of MPD is 34 × 34 µm 2 , as shown in Supplementary Table S1.…”
Section: The Design and Performance Of Mpdmentioning
confidence: 99%
“…The designed MPD is based on the cantilever-structured AlGaN/GaN high-electronmobility transistor (HEMT), in which a magnetic thin film ((Fe 90 Co 10 ) 78 Si 12 B 10 ) is deposited on the front end of the cantilever. [37][38][39][40] The enlarged part is the schematic cross-section of the AlGaN/GaN HEMT, where from top to bottom are AlGaN, AlN, GaN, and Si substrates. The thicknesses of AlGaN, AlN, and GaN layers are 30 nm, 1 nm, and 4.3 µm, respectively, and the active region of MPD is 34 × 34 µm 2 , as shown in Supplementary Table S1.…”
Section: The Design and Performance Of Mpdmentioning
confidence: 99%
“…32 and specific characteristics of the sensor used for this study can be found in Ref. 33. The sensing principle of SAW magnetic field sensors is based on the magneto-elastically induced change of the Young's modulus which leads to a phase modulation of the propagating acoustic wave by the applied magnetic field.…”
Section: Saw Sensormentioning
confidence: 99%
“…FeGaC [ 14 ] and FeCoC [ 15 ] thin films exhibit the highest piezomagnetic coefficients (q) of 10 ppm/Oe. However, for ME MEMS, FeCoSiB with a comparable q = 5 ppm/Oe is mostly used [ 13 , 16 ]. Magnetically soft metglas thin films are most interesting for detecting ultraweak magnetic fields due to the high values of the piezomagnetic coefficient in low magnetic fields, which makes it possible to create self-biased devices [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetically soft metglas thin films are most interesting for detecting ultraweak magnetic fields due to the high values of the piezomagnetic coefficient in low magnetic fields, which makes it possible to create self-biased devices [ 17 ]. However, in the technology of deposition of MS metglas layers, there are several problems associated with the crystallization process in the films due to the heating of substrate during the magnetron sputtering, stresses in the sputtered film and associated magnetic anisotropies [ 16 , 18 ]. In FeCoSiB, MS properties strongly depend on the degree of amorphization of thin films [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%